Exergetic performance evaluation of heat pump systems having various heat sources - Dikici, Aydin; Akbulut, Abdullah (Wiley-Blackwell, 2008)
In this study heat pump systems having different heat sources were investigated experimentally. Solar-assisted heat pump (SAHP), ground source heat Pump (GSHP) and air source heat pump (ASHP) systems for domestic heating were tested. Additionally, their combination systems, such as solar-assisted-ground source heat Pump (SAGSHP), solar-assisted-air source heat pump (SAASHP) and ground-air source heat pump (GSASHP) were tested. All the heat pump systems were designed and constructed in a test room with 60 m(2) floor area in Firat University, Elazig (38.41 degrees N, 39.14 degrees E), Turkey. In evaluating the efficiency of heat pump systems, the most commonly used measure is the energy or the first law efficiency, which is modified to a coefficient of performance for heat pump systems. However, for indicating the possibilities for thermodynamic improvement, inadequate energy analysis and exergy analysis are needed. This study presents an exergetic evaluation of SAHP, GSHP and ASHP and their combination systems. The exergy losses in each of the components of the heat pump systems are determined for average values of experimentally measured parameters. Exergy efficiency in each of the components of the heat pump systems is also determined to assess their performances. The coefficient of performance (COP) of the SAHP, GSHP and ASHP were obtained as 2.95, 2.44 and 2.33, whereas the exergy losses of the refrigerant subsystems were found to be 1.342, 1.705 and 1.942 kW, respectively. The COP of SAGSHP, SAASHP and GSASHP as multiple source heat pump systems were also determined to be 3.36, 2.90 and 2.14, whereas the exergy losses of the refrigerant subsystems were approximately 2.13, 2.996 and 3.113 kW, respectively. In addition, multiple source heat pump systems were compared with single source heat pump systems on the basis of the COP. Exergetic performance coefficient (EPC)is introduced and is applied to the heat pump systems having various heat Sources. The results imply that the functional forms of the EPC and first law efficiency are different. Results show that Ex(loss,total) becomes a minimum value when EPC has a maximum value. Copyright (c) 2008 John Wiley & Sons, Ltd.
Keywords: solar-assisted heat pump; ground source heat pump; air Source heat pump; multiple source heat pump; energy analysis; exergy analysis; exergy efficiency